Ethnic Issues in China's Northwest Frontier Regions and Its Solutions - Yang Liao; Li Meng (RIRAI Publisher, 2020)
The Northwestern Frontier of China is different from the Northwestern China in that it is only a part of the Northwestern China that is close to the border of the country. The geographic space of the northwestern frontier in different periods of Chinese history has changed with the effective governance of the Chinese central government. The ethnic issues in the northwestern frontier have their basic historical background and time and space. The types of ethnic issues in China’s northwest frontier areas are not the same, but they are basically manifested in internal socio-economic and cultural development issues and external ethnic interaction issues, as well as transnational (border) ethnic issues and ethnic religious issues, such as ethnic separatism and extreme religion. Doctrine and violent terrorism are only part of it, not all of it. To this end, it is necessary to